2021
DOI: 10.1080/09712119.2021.1942882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rumen-protected methionine supplementation on dairy cows during early postpartum

Abstract: The objective of this study was to investigate the effects of rumen-protected methionine (RPM) supplementation during early lactation on performance and metabolic parameters of dairy cows. Forty-two Holstein cows were blocked by parity (22 primiparous and 20 multiparous) and calving date, then randomly assigned to two groups, Control and RPM. From calving through 29 ± 8 d in milk, cows received an early lactation diet [1.59 Mcal/kg of DM, 10.7% rumen-degradable protein and 6.5% rumen-undegradable protein] with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Glucose concentration was not affected by dietary treatment, agreeing with previous MHA supplementation in B. indicus -influenced beef heifers ( Moriel et al, 2020 ) and early lactating dairy cows ( Michelotti et al, 2021 ). Collins et al (2019) observed greater serum glucose during late gestational RPMet supplementation in beef cows; however, Palmer et al (2020) noted peripartum MHA supplementation resulted in lower glucose in lactation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Glucose concentration was not affected by dietary treatment, agreeing with previous MHA supplementation in B. indicus -influenced beef heifers ( Moriel et al, 2020 ) and early lactating dairy cows ( Michelotti et al, 2021 ). Collins et al (2019) observed greater serum glucose during late gestational RPMet supplementation in beef cows; however, Palmer et al (2020) noted peripartum MHA supplementation resulted in lower glucose in lactation.…”
Section: Discussionsupporting
confidence: 88%
“… Socha et al (2008) observed a tendency for decreased NEFA during peak lactation and a quadratic decrease over a range of duodenal infusions of methionine during mid lactation; however, there were no effects observed during early lactation or during an earlier study they conducted ( Socha et al, 2005 ). In contrast, early lactational RPMet supplementation in primiparous and multiparous Holstein cows resulted in elevated NEFA ( Michelotti et al, 2021 ). By supplying a more optimal amino acid balance via methionine supplementation, the liver is more effective in exporting NEFA to be used for the synthesis of very low-density lipoproteins ( Socha et al, 2008 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The retrieved studies were screened according to the corresponding inclusion criteria. After excluding the duplicate and unqualified literature, the meta-analysis included 14 studies, as shown in Table 1 [ 1 , 2 , 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. To make it easier to visualize the studied datasets, the mean, maximum, minimum, and standard deviation of each study parameter are summarized in Table A1 of Appendix A .…”
Section: Resultsmentioning
confidence: 99%